2015
DOI: 10.1002/path.4531
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus pre‐S2 mutant large surface protein inhibits DNA double‐strand break repair and leads to genome instability in hepatocarcinogenesis

Abstract: Although hepatitis B virus (HBV) has been established to cause hepatocellular carcinoma (HCC), the exact mechanism remains to be clarified. Type II ground glass hepatocytes (GGHs) harbouring the HBV pre-S2 mutant large surface protein (LHBS) have been recognized as a morphologically distinct hallmark of HCC in the advanced stages of chronic HBV infection. Considering its preneoplastic nature, we hypothesized that type II GGH may exhibit high genomic instability, which is important for the carcinogenic process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
0
36
1
Order By: Relevance
“…Snap-frozen protein lysates of the surgically resected tumorous and peritumorous HCC tissues of patients (n 5 22) at NCKUH were analyzed for LHBS expression by western blotting, following the protocol described. (29) The wild-type (n 5 10) and pre-S 2 mutant (n 5 12) cases were preidentified by pre-S gene chip analysis. (30) LHBS was detected using an in-house-developed mouse monoclonal antibody (clone 7-21-5) recognizing the pre-S 1 region.…”
Section: Western Blotting Of Lhbs In Hcc Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Snap-frozen protein lysates of the surgically resected tumorous and peritumorous HCC tissues of patients (n 5 22) at NCKUH were analyzed for LHBS expression by western blotting, following the protocol described. (29) The wild-type (n 5 10) and pre-S 2 mutant (n 5 12) cases were preidentified by pre-S gene chip analysis. (30) LHBS was detected using an in-house-developed mouse monoclonal antibody (clone 7-21-5) recognizing the pre-S 1 region.…”
Section: Western Blotting Of Lhbs In Hcc Tissuesmentioning
confidence: 99%
“…Pre‐S 2 mutant LHBS protein also directly interacts with c‐Jun activation domain‐binding protein 1, which degrades cyclin‐dependent kinase inhibitor p27 Kip1 and, consequently, G 1 –S‐phase cell‐cycle progression, even in the presence of DNA damage . We also recently reported that pre‐S 2 mutant LHBS transgenic mice were genomically unstable, which was indicated by global gene copy number variations significantly higher than those in age‐matched HBx mice. This indicates that the pre‐S 2 mutant LHBS is the main viral oncoprotein which induces host genomic instability and triggers carcinogenesis.…”
mentioning
confidence: 99%
“…Independent of the ER stress pathways, preS2-LHBS directly interacted with c-Jun activation domain-binding protein 1 (JAB1), which led to the degradation of p27 and thereby promoted the hyperphosphorylation of retinoblastoma [ 18 ]. In addition, preS2-LHBS directly interacted with importin α1, thereby blocked the nuclear transport of an essential DNA repair and recombinant factor, Nijmegen breakage syndrome 1 (NBS1), upon DNA damage, and subsequently impeded DNA double-stranded break repair [ 19 ]. Notably, transgenic mice carrying preS2-LHBS displayed higher genomic instability than transgenic mice carrying HBV X protein using array-based comparative genomic hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…These deletion mutations may induce defective immunity against HBV . The accumulation of in‐frame pre‐S2 mutant large surface protein inhibits hepatocyte DNA double‐strand break repair and is associated with HCC tumourigenesis . On the other hand, the presence of truncated pre‐S/S protein has the function of transcriptional transactivator .…”
Section: Aetiological Association and Risk Stratification Of Hbv‐relamentioning
confidence: 99%